A novel approach in the intraoperative management of ovotesticular DSD. Issue 6 (December 2020) - Delforge, Xavier; Brachet, Cécile; Damry, Nasroola; Segers, Valérie; Luyckx, Stephane; Heinrichs, Claudine; Khelif, Karim
Summary: Ovotesticular disorder of sex development (OTD) management remains challenging. In OTD, cautious gonadal evaluation and separation of ovarian and testicular components might be required to avoid virilization of a patient with female identity. Herein we report our minimal invasive approach in this very rare condition. The gonads are externalized under laparoscopic control through trocar openings. Intraoperative ovotesticular ultrasonography (US) is used for clear identification of ovarian and testicular tissue which can then be safely separated. We strongly promote the use of a minimal invasive approach in the management of these patients undergoing long term treatment and often multiple procedures.